Pembekalan Ilmu Perhitungan Digital Berbasis Stand Alone dan Cloud Melalui Excel dan Spreadsheet - Rizky Pradana; Riri Irawati; Agnes Aryasanti; Dwi Achadiani; Hendri Irawan (Journal of Appropriate Technology for Community Services, 2021)
The current prolonged pandemic requires every individual to do social distancing and physical distancing. This made a difference study and work patterns. In order to overcome this and prepare workforce in the future, it requires an habituation of learning patterns and work through devices you own from your home or residence. To improve the performance of the learning process, an additional learning mechanism is needed on the use of technology, especially in the field of digital calculations. In order to solve this problem on the partner's side, the team made a solution, namely in the form of provisioning with a training pattern using Microsoft Excel which is the basis for a general calculation pattern commonly used both in the world of education and in the world of work and also the use of Google Spreadsheets. The method used in this debriefing is learning by doing, which is a method where every student who follows it will go directly to practice by following instructions from the training instructor from the PKM team. Based on the training provided, the average post test result is 76.6 from the 0-100 range, or increasment 23,28% at from Pre Test to Post test